Деформирование трехслойного стержня со сжимаемым заполнителем в нейтронном потоке - Старовойтов, Э.И.; Леоненко, Д.В. (Прикладная механика, 2020)
В статье исследовано деформирование трехслойного стержня прямоугольного поперечного сечения со сжимаемым заполнителем, составленного из физически нелинейных материалов и находящегося в нейтронном потоке. Досліджено деформування тришарового пружнопластичного стержня зі стисливим заповнювачем у нейтронному потоці. Для опису кінематики несиметричного по товщині пакета прийнято гіпотези ламаної лінії: в тонких несучих шарах справедлива гіпотеза Бернуллі; в стисливому по товщині заповнювачі виконується гіпотеза Тимошенка з лінійною апроксимацією переміщень по товщині шару. Враховано роботу заповнювача в тангенціальному напрямку. Фізичні співвідношення зв'язку напружень і деформацій відповідають теорії малих пружнопластичних деформацій. Систему диференціальних рівнянь рівноваги отримано варіаційним методом. На границі прийнято кінематичні умови вільного опертя торців стержня на нерухомі в просторі жорсткі опори. Розв'язання крайової задачі зведено до визначення чотирьох функцій і прогинів і поздовжніх переміщень серединних поверхонь несучих шарів. Аналітичний розв'язок отримано на основі методу пружних розв'язків. Проведено його чисельний аналіз у випадку рівномірно розподіленого навантаження. The deformation of a three-layer elastoplastic bar with a compressible filler in the neutron flux is studied. To describe the kinematics of an asymmetric over thickness package, the hypotheses of a broken line is accepted: the Bernoulli’s hypothesis is true in the thin bearing layers; the Timoshenko’s hypothesis is true in the compressible over thickness filler with a linear approximation of displacements over the layer thickness. The filler’s work in the tangential direction is taken into account. The physical stress-strain relations correspond to the theory of small elastoplastic deformations. A system of differential equilibrium equations is obtained by the variational method. The kinematic conditions of simply supported faces of the bar on the immovable in space rigid supports are assumed on the boundary. The solving the boundary problem is reduced to the search for four functions, namely: deflections and longitudinal displacements of the medial surfaces of the bearing layers. An analytical solution is obtained by the method of elastic solutions. Its numerical analysis is performed for the case of uniformly distributed loading.